Estudio de la gestión energética en la UEB cárnicos bayamo. valorización energética de los residuos sólidos derivados del procesamiento cárnico - Arcos Narváez, Willian David (2016)
The present work is focused on energy assessment and determination of the potential for biogas production in the UEB Carnicos Bayamo since 2012-2014; revealing that electricity and fuel Fuel-Oil are the most influential with 58.04 and 33.90% in energy consumption. During the study the potential of biogas production from solid waste analyzed that by design simplex mixtures lattice, followed by an analysis of responses allowed model and optimize methane production in anaerobic co-digestion of three different substrates generated in plants meat processing: manure, rumen and wastewater. An analysis of the results it is found that the best fit fueel special cubic model, with values of R2 and R2ajustado of 95.13% and 90.96% respectively, which allowed us to determine the biogas produced daily. Finally, the sequence design biodigesters fixed dome type of GBV which concluded that the construction of two 47.5 m3 biodigesters, which produce a daily volume of approximately 15 m3 of biogas is necessary is used.